2011
DOI: 10.21432/t2hp42
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse critique des connaissances sur l'écriture électronique à l'aide du blogue au primaire et au secondaire

Abstract: RésuméCet article présente une synthèse critique des connaissances qui s'inscrit dans la foulée des travaux du Comité d'experts sur l'apprentissage de l'écriture qui, en janvier 2008, a publié un rapport intitulé « Mieux soutenir le développement de la compétence à écrire ». La synthèse s'est concentrée sur les textes à caractère scientifique traitant de la pratique d'écriture électronique du blogue dans les classes du primaire et du secondaire. La période couverte s'étend de janvier 2004 à mai 2010. Les résul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Quant à la coélaboration de connaissances, il s'agit de la traduction de knowledge building, plus tard devenu knowledge creation, pour bien mettre en exergue l'accent mis par ce modèle sur l'élaboration d'un savoir collectif plutôt qu'individuel (Allaire et Laferrière, 2013). Les élèves des classes qui travaillent selon ce modèle cherchent donc délibérément à faire progresser leur compréhension d'un objet qu'ils examinent, telle une équipe de petits chercheurs.…”
Section: éCriture Collaborativeunclassified
“…Quant à la coélaboration de connaissances, il s'agit de la traduction de knowledge building, plus tard devenu knowledge creation, pour bien mettre en exergue l'accent mis par ce modèle sur l'élaboration d'un savoir collectif plutôt qu'individuel (Allaire et Laferrière, 2013). Les élèves des classes qui travaillent selon ce modèle cherchent donc délibérément à faire progresser leur compréhension d'un objet qu'ils examinent, telle une équipe de petits chercheurs.…”
Section: éCriture Collaborativeunclassified
“…Learning environments integrating blogs would seem to encourage student motivation. A literature review conducted on this topic has highlighted the fact that few studies have paid specific attention to the writing process and the content and quality of texts disseminated through such a tool (Allaire, Thériault & Lalancette, 2011). Acknowledging this opens up new possibilities for exploring more precise aspects of developing writing competency, and where the blog holds promising pedagogical potential in the eyes of many (Downes, 2006;Ward, 2004).…”
Section: Le Soutien D'enseignants Et Les Stratégies D'écriture D'élèves Du Primaire Dans Un Environnement D'apprentissage En Réseau Intégmentioning
confidence: 99%
“…A pedagogical counselor working on the integration of ICTs in the language arts recommended participants in this case study. Two main criteria guided the selection of cases (Allaire, Thériault & Lalancette, 2011). On one hand, teachers had to explicitly intend to use a blog in order to develop students' writing competency (affective and/or cognitive aspects).…”
Section: Choice Of Participating Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent literature review has shown that few studies have systematically documented how networked learning environment (Laferrière, 1999) supported by Web 2.0 tools such as blogs can have an impact on the development of the writing processes over a full academic year at the elementary-school level (Allaire, Thériault & Lalancette, 2010, 2011. Indeed, most studies conducted that we have taken inventory of gave an account of research carried out in the context of higher or continuing education.…”
Section: Introductionmentioning
confidence: 99%